Drought-induced starvation of aardvarks in the Kalahari: an indirect effect of climate change. (31st July 2017) - Rey, Benjamin; Fuller, Andrea; Mitchell, Duncan; Meyer, Leith C. R.; Hetem, Robyn S.
Abstract : Aardvarks ( Orycteropus afer ) are elusive burrowing mammals, predominantly nocturnal and distributed widely throughout Africa except for arid deserts. Their survival may be threatened by climate change via direct and indirect effects of increasing heat and aridity. To measure their current physiological plasticity, we implanted biologgers into six adult aardvarks resident in the semi-arid Kalahari. Following a particularly dry and hot summer, five of the study aardvarks and 11 other aardvarks at the study site died. Body temperature records revealed homeothermy (35.4–37.2°C) initially, but heterothermy increased progressively through the summer, with declining troughs in the nychthemeral rhythm of body temperature reaching as low as 25°C before death, likely due to starvation. Activity patterns shifted from the normal nocturnal to a diurnal mode. Our results do not bode well for the future of aardvarks facing climate change. Extirpation of aardvarks, which play a key role as ecosystem engineers, may disrupt stability of African ecosystems.